A Family of Dinuclear Iron(II) SCO Compounds Based on a 1, 3, 4‐Thiadiazole Bridging Ligand1. Issue 22 (12th June 2015) - Herold, Christian F.; Carrella, Luca M.; Rentschler, Eva
Abstract: A new family of dinuclear iron(II) spin‐crossover (SCO) compounds with the formula [Fe2 (μ‐L)2 ]X4, with three different counteranions [X = BF4 – (1 ), ClO4 – (2 ) and F3 CSO3 – (3 )], was prepared and characterized by single‐crystal X‐ray diffraction, variable‐temperature magnetic susceptibility and Mössbauer measurements. These are the first dinuclear iron(II) SCO complexes with a 1, 3, 4‐thiadiazole bridging ligand L with L = 2, 5‐bis[(2‐pyridylmethyl)amino]methyl‐1, 3, 4‐thiadiazole. The magnetic measurements reveal a gradual and incomplete SCO of the three compounds around room temperature, starting from a diamagnetic [LS–LS] state. The diamagnetic ground state is in agreement with the single‐crystal X‐ray diffraction and Mössbauer data. Abstract : Herein we present a new 1, 3, 4‐thiadiazole bridging ligand and three spin‐crossover active dinuclear iron(II) compounds. The complexes show promising magnetic properties with a diamagnetic [LS–LS] ground state at low temperatures and represent a great starting point to explore this new family of dinuclear SCO compounds.